2013
DOI: 10.1016/j.jad.2012.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of motor abnormalities in untreated patients with major depressive disorder

Abstract: The primary purpose of this study was to examine motor physiology disturbances in a group of patients with untreated major depressive disorder using sensitive instrumental procedures. The secondary aim of the study was to examine the relationship of the affective symptom state to these motor assessments. The authors studied 40 individuals meeting DSM-IV criteria for unipolar major depressive disorder and 40 healthy comparison subjects. Electromechanical measures of force steadiness (FS), simple reaction time (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Walther et al [13] recently found that MDD patients displayed associations between resting state cerebral blood flow and activity level in the right orbito-frontal cortex and left supplemental motor area (SMA). These findings are consistent with the assumption of dopamine deficiency responsible for the motor retardation in MDD patients [1]. Against the role of the prefrontal cortex and SMA in human balance control, physical activity influences brain-related function and outcomes, through effects on the striatal dopamine system [14].…”
Section: Totalsupporting
confidence: 88%
See 1 more Smart Citation
“…Walther et al [13] recently found that MDD patients displayed associations between resting state cerebral blood flow and activity level in the right orbito-frontal cortex and left supplemental motor area (SMA). These findings are consistent with the assumption of dopamine deficiency responsible for the motor retardation in MDD patients [1]. Against the role of the prefrontal cortex and SMA in human balance control, physical activity influences brain-related function and outcomes, through effects on the striatal dopamine system [14].…”
Section: Totalsupporting
confidence: 88%
“…Psychomotor disorders are more prevalent in depression than in healthy controls, and are often related to the severity of clinical state [1]. Numerous studies have described a strong association between motor disorders and early depressive symptoms (and associated cognitive decline) [2,3], and this association is supported by (depressed) state-related balance impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Handwriting samples are being obtained to compute Velocity Scaling to index PmR [76]. Lower values of Velocity Scaling reflect the slowing or inability to increase pen movement velocity across shorter and longer target distances, and have been linked to motor slowing in several clinical populations [17,18,77]. Handwriting samples are acquired using strokes, which will be segmented and processed for target variables: peak vertical velocity and absolute size of stroke.…”
Section: Lab Measurement Of Pmrmentioning
confidence: 99%
“…It should be noted that unipolar depression is also associated with various psychomotor abnormalities (e.g., see Sobin and Sackeim [19] and Peralta and Cuesta [23] for reviews; see also Lohr et al [36]). The associations between depression as a symptom domain and motor variables will be explored in the current study.…”
Section: Introductionmentioning
confidence: 99%